Consumer Response and Their Level of Satisfaction towards Nepalese Coffee - Karki, Yogendra Kumar; Regmi, Punya Prasad (International Journal of Applied Sciences and Biotechnology, 2016)
Coffee is important beverages of Nepalese farming society having export potentiality for its unique characteristics as majority of coffee are grown in different microclimates with organic in nature. Production of coffee and its plantation area is in increasing trend every year. In the same situation individuals taste is changing towards coffee than other beverages and are forced to buy from different countries to meet the demand of coffee neglecting quality of Nepalese coffee. There is important role of different actors in coffee value chain and consumers play important role as they decide on the value of coffee serving after various step of processing. This study was done in Kathmandu and Lalitpur districts of Nepal to know the preferences and satisfaction level of coffee consumers. Majority of the consumers were satisfied with foreign coffee and they prefer foreign coffee mostly due to high price of Nepalese coffee and also due to lack of awareness on Nepalese coffee. Foreign peoples were found to prefer foreign coffee in comparison to Nepalese coffee (χ²= 23.02***) and generally drink three cup per day (χ²= 13.67***) while Nepalese consumer drink two cup of coffee per day on an average. The survey showed that high market price for Nepalese coffee is major reason for less consumption of Nepalese coffee. Int J Appl Sci Biotechnol, Vol 4(2): 213-216